2019
DOI: 10.3390/f10100894
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Changing Temperature on Gross N Transformation Rates in Acidic Subtropical Forest Soils

Abstract: Soil temperature change caused by global warming could affect microbial-mediated soil nitrogen (N) transformations. Gross N transformation rates can provide process-based information about abiotic–biotic relationships, but most previous studies have focused on net rates. This study aimed to investigate the responses of gross rates of soil N transformation to temperature change in a subtropical acidic coniferous forest soil. A 15N tracing experiment with a temperature gradient was carried out. The results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…In this study, the results showed that gross ammonification rates increased exponentially as the incubation temperature increased from 5 to 35 °C in SL10 and SL20 soils ( R 2 > 0.99, p < 0.01, Figure 2 a), which was consistent with 15 N tracing studies in subtropical broad-leaved forest and coniferous forest soils [ 12 , 44 , 45 ]. In short, ammonification in soil is composed of two processes: decomposition of labile organic N and decomposition of recalcitrant organic N [ 45 ]. The decomposition of recalcitrant organic N is less temperature-sensitive than that of labile organic N in subtropical forests, so it can only be stimulated at higher temperatures [ 44 ].…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the results showed that gross ammonification rates increased exponentially as the incubation temperature increased from 5 to 35 °C in SL10 and SL20 soils ( R 2 > 0.99, p < 0.01, Figure 2 a), which was consistent with 15 N tracing studies in subtropical broad-leaved forest and coniferous forest soils [ 12 , 44 , 45 ]. In short, ammonification in soil is composed of two processes: decomposition of labile organic N and decomposition of recalcitrant organic N [ 45 ]. The decomposition of recalcitrant organic N is less temperature-sensitive than that of labile organic N in subtropical forests, so it can only be stimulated at higher temperatures [ 44 ].…”
Section: Discussionsupporting
confidence: 89%
“…1 ). Earlier research also suggests that ammonification is a temperature sensitive microbial mediated mineralization process 46 48 and an increase in temperature upto 25 °C will significantly increase the transformation rate of N 49 . The trend for nitrate (NO 3 − N) concentration varied between 8.37 and 81.88 µg NO 3 – N g –1 DW in coprolites influenced by different treatments.…”
Section: Resultsmentioning
confidence: 98%
“…Previous research findings suggest that earthworm gut and castings tend to have more active heterotrophic microbes that positively influence the amounts of extractable NO 3 – -N in upper layer of soil 51 53 moreover, increased NO 3 − concentration in coprolites is a good indicator of the nitrification process and abundance of nitrifiers 23 , 25 , 54 56 . It is also reported that the heterotrophic nitrification has an optimum temperature requirement of 15 °C 57 while, it exceeds over autotrophic nitrification if the temperature is increased to 35 °C 49 . Further, we confirm that the heterotrophic nitrification is an ecosystem dependent process which is directly dependent on substrate type, microbial diversity and abundance.…”
Section: Resultsmentioning
confidence: 98%
“…Nitrification increases with MAT (p < 0.001) (Figure 4e) and may outcompete immobilization for soil NH 4 + . 57 Dan et al (2019) 58 and Lan et al (2014) 59 reported that the effect of increasing temperature (5−35 °C) on nitrification was greater than that on immobilization. Therefore, the N/I ratio and potential risk of nitrogen loss in tropical and subtropical regions (with high MAT) are higher than those in other climatic regions.…”
Section: ■ Discussionmentioning
confidence: 99%